Pelo mar absoluto, navegam os versos de Cecília Meireles / On the absolute sea navigate the verses of Cecília Meireles - Almeida, Laura Beatriz Fonseca de (Revista de Letras, 2007)
Com base na análise do poema “Mar absoluto” de Cecília Meireles, poema que abre e dá nome ao volume de poesias de 1945, discuto a artesania poética moderna da poeta que elege o mar para um dos temas da sua poesia. Based on the analysis of the poem “Mar absoluto” by Cecília Meireles, poem which begins and gives the name to the volume of 1945, I discuss the modern poetic art of the poet who chooses the sea as one of the themes of her poetry.